TRANSFORMATION OF TRADITIONAL SPACE: NEGOTIATING ECONOMIC–CULTURAL CAPITAL IN THE DEVELOPMENT OF THE CANGGU, BALI TOURISM DESTINATION - Daniswara, Nirwasita; Sinambela, Adi Tri Paldi (Faculty of Islamic Economic and Business - Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstract: Tourism in the era of neo-capitalism has transformed customary spaces from meaningful cultural landscapes into curated commodities tailored to global tastes. Addressing the gap in understanding how customary law operates as a mediating force within the architecture of tourism power, this study explores the negotiation between economic and cultural capital in the spatial production of Canggu, Bali. Employing an interpretive qualitative case study design, data were collected through participatory and non-participatory observation, semi-structured interviews with customary leaders (prajuru adat), pecalang (traditional guards), local architects, business actors, and document analysis, and triangulated across multiple methods. Integrating Pierre Bourdieu’s framework of economic, cultural, and symbolic capital with Henri Lefebvre’s theory of spatial production comprising spatial practices, representations of space, and representational spaces the findings reveal that: (1) commodification operates through “market-oriented spatial selection” that marginalizes everyday practices and intangible values; (2) customary authority mobilizes symbolic capital such as sacred temple radii, architectural pakem (traditional design standards), and river setbacks to moderate capital expansion and maintain socio-ecological cohesion; (3) the hybridization of traditional and modern architecture serves as a “value signal,” simultaneously enhancing market appeal and becoming an arena of meaning contestation; and (4) a dual governance regime, combining state regulations and awig-awig (customary law), establishes a configuration that is both mediating and restrictive, with customary sanctions and formal legal references as instruments of enforcement. Theoretically, this study extends debates on cultural tourism by formalizing cross-capital conversions in spatial production, while practically, it proposes a policy architecture that integrates formal planning mechanisms with customary instruments to safeguard intangible and ecological values without diminishing economic benefits. Policy implications include the standardization of sacred–ecological corridors, audits of cultural theatricalization, and community legitimacy–based benefit-sharing schemes. Keywords: spatial production; cultural and symbolic capital; customary law; commodification; tourism governance; Canggu Bali. Abstract: Pariwisata di era neo-kapitalisme mendorong transformasi ruang adat dari lanskap bermakna menjadi komoditas yang dikurasi bagi selera global. Berangkat dari kekosongan kajian mengenai bagaimana hukum adat bekerja sebagai penyangga dalam arsitektur kuasa pariwisata, studi ini menelaah negosiasi modal ekonomi dan kultural dalam produksi ruang destinasi Canggu, Bali. Menggunakan pendekatan kualitatif interpretatif dengan desain studi kasus, data dikumpulkan melalui observasi partisipatif/non-partisipatif, wawancara semi-terstruktur dengan prajuru adat, pecalang, arsitek lokal, pelaku usaha, serta telaah dokumen, dan ditriangulasi lintas metode. Dengan mengintegrasikan kerangka Pierre Bourdieu (modal ekonomi, budaya, simbolik) dan Henri Lefebvre (praktik spasial, representasi ruang, ruang representasional), temuan menunjukkan: (1) komodifikasi berlangsung melalui “seleksi spasial berorientasi pasar” yang menyingkirkan elemen keseharian dan nilai takbenda; (2) otoritas adat mengaktifkan kapital simbolik seperti halnya radius kesakralan pura, pakem arsitektur, dan sempadan sungai untuk memoderasi ekspansi kapital dan menjaga kohesi sosial-ekologis; (3) hibridisasi arsitektur tradisional dan modern berfungsi sebagai “signal nilai” yang menaikkan daya jual sekaligus menjadi arena perebutan makna; (4) rezim ganda (aturan negara dan awig-awig) membentuk konfigurasi tata kelola yang bersifat mediasi sekaligus pembatas, dengan sanksi adat dan rujukan hukum formal sebagai instrumen penegakan. Secara teoretis, studi ini memperluas perdebatan kepentingan wisata dan budaya dengan memformalkan konversi lintas-modal dalam produksi ruang yang mengusulkan arsitektur kebijakan yang menyinergikan perencanaan formal dengan instrumen adat untuk melindungi nilai takbenda dan daya dukung ekologis tanpa meniadakan manfaat ekonomi. Implikasi kebijakan meliputi standardisasi koridor sakral dan ekologis, audit teaterisasi budaya, dan skema bagi-hasil berbasis legitimasi komunitas. Keywords: produksi ruang; modal budaya & simbolik; hukum adat; komodifikasi; tata kelola pariwisata; Canggu Bali.